ESG Disclosure and Tax Aggressiveness under Regulatory Pressure: Empirical Evidence from IDX Companies - Ahmad Bukhori Muslim; Benny Oktaviano; Immanuel Setiawan Silitonga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study investigates the effect of Environmental, Social, and Governance (ESG) disclosure on corporate tax aggressiveness under regulatory pressure among companies listed on the Indonesia Stock Exchange (IDX). The increasing adoption of ESG reporting and the strengthening of sustainability regulations have intensified the need to understand whether greater corporate transparency contributes to more responsible tax behavior. Using a quantitative research design, this study analyzes panel data from non-financial IDX-listed companies during the 2021–2025 period. Secondary data are collected from annual reports, sustainability reports, and audited financial statements. Panel data regression with moderation analysis is employed to examine the relationship between ESG disclosure, regulatory pressure, and tax aggressiveness while controlling for firm characteristics. The findings indicate that ESG disclosure has a significant negative effect on tax aggressiveness, suggesting that firms with higher ESG transparency are less likely to engage in aggressive tax planning. Furthermore, regulatory pressure strengthens this relationship by encouraging greater compliance with tax and sustainability regulations. These findings contribute to the growing literature on ESG and corporate taxation by demonstrating the importance of institutional enforcement in promoting ethical corporate behavior. The study also provides practical implications for policymakers, investors, and corporate managers in strengthening ESG regulations and improving tax governance to support sustainable business practices.